2000
DOI: 10.1007/s11661-000-0115-1
|View full text |Cite
|
Sign up to set email alerts
|

Study of microstructure of low-temperature plasma-nitrided AISI 304 stainless steel

Abstract: The microstructure of the low-temperature plasma-nitrided layer on AISI 304 austenitic stainless steel was studied by transmission electron microscopy (TEM). The results show that the surface of the layer consists of a supersaturated solid solution (␥ Ј N ) based on the ␥ Ј-Fe 4 N phase whose electron diffraction pattern (EDP) has a strong diffuse scattering effect resulting from supersaturating nitrogen (above 20 at. pct) and ͗110͘ streaks arising from matrix elastic strain due to the formation of paired or c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…In the same micrograph it is possible to identify "colonies" (marked with white arrows in Fig. 6) on the surface of the grain "B" whose morphology is quite similar to that observed in nitrided layers investigated by Mitchell et al [21] and Xu and colleagues [22]. These colonies result from localized expanded austenite decomposition and they display a lamellar type microstructure composed by ferrite and cubic chromium nitride [13,21].…”
Section: Tem Analysissupporting
confidence: 56%
“…In the same micrograph it is possible to identify "colonies" (marked with white arrows in Fig. 6) on the surface of the grain "B" whose morphology is quite similar to that observed in nitrided layers investigated by Mitchell et al [21] and Xu and colleagues [22]. These colonies result from localized expanded austenite decomposition and they display a lamellar type microstructure composed by ferrite and cubic chromium nitride [13,21].…”
Section: Tem Analysissupporting
confidence: 56%
“…The resulting depth variation of the composition has several implications for the observed X-ray diffractograms. The compositional inhomogeneity within the investigated depth range causes asymmetric broadening and the induced macrostress gradient over the expanded austenite zone causes hkl-dependent shifts of the diffraction peaks (Ö ztü rk & Williamson, 1995;Xu et al, 2000;Christiansen et al, 2010). Asymmetric broadening is also anticipated from texture gradients (Riviè re et al, 2007).…”
Section: Introductionmentioning
confidence: 98%
“…The formation of nitrides is believed to be almost suppressed at nitriding temperatures around 400 1C or below, due to sluggish chromium diffusion, thus preserving corrosion resistance [6]. However, for long nitriding times CrN does form, especially at the surface [7][8][9]. We have recently reported that nanometer-sized precipitates do form after nitriding for 30 h at 400 1C in AISI 304L [10].…”
Section: Introductionmentioning
confidence: 99%